Apertochrysa (Neuroptera: Chrysopidae): A heterogeneric phantom? - Mochizuki, Atsushi; Henry, Charles S.; Duelli, Peter (Zootaxa, 2017)
The small lacewing genus Apertochrysa comprises species from Africa, Asia and Australia. All lack a tignum, but otherwise resemble distantly related genera. We show that Apertochrysa does not form a monophyletic clade, based on analyses of molecular sequence data and morphological traits such as the presence and shape of the male gonapsis, wing venation, and larval setae. Apertochrysa kichijoi forms a clade with Eremochrysa, Suarius and Chrysemosa, whereas A. albolineatoides belongs to a clade that includes Cunctochrysa. Apertochrysa albolineatoides should become a new combination as Cunctochrysa albolineatoides, while A. kichijoi will have to be transferred to a new genus. The Australian A. edwardsi, the African A. eurydera and the type species of the genus Apertochrysa, A. umbrosa, join the large Pseudomallada group. Relationships of A. umbrosa are less certain, because for it we could amplify only one of the three nuclear genes used in the overall analysis. However, in all morphological traits tested, that species strongly resembles A. edwardsi and A. eurydera and thus is very likely just another exceptional Pseudomallada lacking a tignum. The fate of the genus name Apertochrysa depends on additional molecular and morphological analyses of A. umbrosa.